Raspberry danish murder [large type] - Fluke, Joanne, 1943- (Fluke, Joanne, 1943- Hannah Swensen mystery., 2018)
Throwing herself into the holiday season in the aftermath of her husband Ross' disappearance, Hannah Swensen investigates the murder of her husband's television-station assistant, who had been driving Ross' car and working from his office at the time of his death.